KAJIAN EPIGRAFIS PRASASTI BABAHAN - Hedwi Prihatmoko (Balai Arkeologi Bali, 2016)
Babahan inscriptions are not fully published until now. Historical data which were revealed from Babahan inscriptions are very limited. This research aims to reconstruct cultural history and reveal social institutions depicted in Babahan inscriptions in order to add historical data of ancient Bali. The data were collected through observation, such as physical attributes, material, amount of plates, amount of lines on every plate, type of letters, and type of languages, then continued with literature study. Analysis was done through transliteration, editing, and translation. Interpretation is presented descriptively by placing it in the context of ancient Bali history. The result of this research is that Babahan inscriptions could be grouped into two groups. Group one uses ancient Balinese letter and language which was issued by King Ugrasena. Group two uses ancient Javanese letter and language which was issued by King Wālaprabhu. The social institutions, depicted by Babahan inscriptions, are political and religious institutions. Political institution is depicted through the mentions of official positions in the government and social order in society. Religious institution is depicted through the mentions of official positions of religious leaders, sacred places, the idea of king leadership, and ṡapatha. Prasasti Babahan merupakan kelompok prasasti yang belum diterbitkan secara utuh. Data sejarah yang diungkapkan dari Prasasti Babahan masih sangat terbatas hingga saat ini. Penelitian ini bertujuan untuk melakukan rekonstruksi sejarah kebudayaan dan mengungkapkan gambaran pranata sosial yang ada di dalamnya untuk melengkapi penyusunan sejarah Bali kuno. Pengumpulan data dilakukan melalui pengamatan langsung terhadap unsur fisik, bahan, jumlah lempeng, jumlah baris tiap lempeng, jenis aksara, dan jenis bahasa, serta studi kepustakaan. Analisis dilakukan melalui alih aksara, penyuntingan prasasti, dan alih bahasa. Penafsiran disajikan secara deskriptif dengan menempatkannya di dalam konteks sejarah Bali kuno. Hasil penelitian ini adalah Prasasti Babahan merupakan prasasti sima yang terdiri dari dua kelompok. Kelompok I menggunakan aksara dan bahasa Bali kuno yang dikeluarkan oleh Raja Ugrasena, sedangkan kelompok II menggunakan aksara dan bahasa Jawa kuno yang dikeluarkan oleh Raja Wālaprabhu. Pranata sosial yang tampak dari Prasasti Babahan adalah pranata politik dan agama. Pranata politik digambarkan melalui penyebutan nama jabatan di pemerintahan dan tatanan sosial di masyarakat. Pranata agama digambarkan melalui penyebutan nama jabatan pemuka agama, tempat suci keagamaan, gagasan kepemimpinan raja, dan ṡapatha.